Effet de la température sur la croissance et la sporulation de Colletotrichum sp. agent de l’anthracnose des agrumes et spécialisation parasitaire de l’agent pathogène dans la région de Mostaganem - NAIT MESSAOUD, Tanina (My University, 2018)
Anthracnose disease caused by the pathogenic fungus Colletotrichum sp is one of the major constraints to citrus production worldwide. The present study aims to study both the morphological and cultural characteristics, the effect of temperature on the growth and sporulation of the pathogen and its parasitic specialization towards two plant species tomato (kawa) and chilli (biskra). ). Our study is carried out at the level of a Clementine and Thomson Navel vergé presenting Anthracnose disease, located in the Bougirate region, north-east of Mostaganem. In order to carry out this study, eight monospore culture isolates of Colletotrichum sp were obtained from Clementine leaf samples showing the symptoms of anthracnose, the analysis of microscopic, macroscopic and conidial size variation. showed significant variation between isolates so temperature has an impact on growth and sporulation. The pathogenicity test showed a difference in degree of severity between the Colletotrichum sp isolates and their pathogenic power by adding to the plant species, the tomato is more sensitive by adding pepper.
Keywords: Colletotrichum sp.; Anthracnose; Agrume; tomate; piment; pathogénicité; pathogenicity